ANALISIS KEMAUAN DAN KEMAMPUAN MEMBAYAR SERTA PREDIKSI POLA PERJALANAN KONSUMEN RUTE PASAR KOTA KARANG – PASAR LEMPASING BANDAR LAMPUNG - Aditya Mahatidanar Hidayat; Prasetya Wibisono (Universitas Bandar Lampung, 2017)
The development of livelihood activities in Bandar Lampung City precisely in the area of Jalan Laksamana R.E.Martadinata has been very rapid which will also generate an increase in traffic flow, so that efforts are needed to improve transportation services. This study aims to determine the rates given by the Pasar Kota Karang - Lempasing Market Bandar Lampung route, reviewing whether the socio- economic characteristics or attributes of transportation services are the most dominant, the ability of consumers to pay and know the pattern of travel. The research was conducted by means of a survey to find out the travel pattern and the willingness and ability of consumers to determine transportation service tariffs with the service attributes provided. The survey object is the community around Jalan Laksamana R.E.Martadinata, starting from the intersection of Jalan Ikan Sebelah to the TPI Lempasing. The data obtained are then processed with the SPSS v.24 software program. The tariff that is most given by consumers to the Bus Rapid Trans service plan with Pasar Kota Karang route - Bandar Lampung Lempasing Market based on the willingness to pay is Rp.2000,- . Based on the ability to pay by looking at the results of the regression model obtained, it is obtained information about the number of coefficients of socio-economic factors with variables of gender, age, income, education, intensity of use of BRT, residence, transportation costs, mode of transportation, and destination of Rp. 3.231,- . For the number of coefficients of service attribute factors which consist of student tariffs, operating hours, availability of bus stops and availability of goods, there are no significant results that affect the tariff determination. The most popular travel origins are number 1 with locations in the coral city market and the most popular travel destinations, number 7 with locations on the marketplace.